Characterization Of Aromatic, Morphological, And Genetic Diversity In Gardenia (Gardenia jasminoides) For Sustainable Fragrance Applications - Gajapathy, K.; Anushika, C.M.; Terensan, S. (National Science and Technology Commission, 6th floor, Wing D, Sethsiripaya Stage II, Battaramulla., 2026)
Aromatic plants are widely distributed in nature, with many species cultivated specifically to produce essential oils. Gardenia (Gardenia jasminoides) is a flowering perennial with white, sweet-scented flowers, which belongs to the family of Rubiaceae [1]. The plants grow to between two and five feet tall and have glossy light green leaves. It is cultivated largely for decor, perfume, and even the pharmaceutical industry. As an indigenous plant, its utilization aligns with the growing emphasis on sustainable and eco-friendly agricultural practices. Gardenia essential oil is prioritized for its sweet, floral fragrance and is commonly used in perfumery and aromatherapy due to its calming and mood-uplifting properties [2]. This study aims to evaluate the morphological and chemical characterization of these species, utilizing DNA markers and Gas Chromatography-Mass Spectrometry (GC-MS) to achieve precise species identification and detailed profiling of volatile organic compounds (VOCs) present in Gardenia to support its sustainable use and value-added applications. Understanding the genetic diversity and chemical profile is essential for ensuring the optimal use of Gardenia in both perfumery and medicinal fields. The findings could support future breeding programs and the genetic enhancement of fragrance, contributing to both the ornamental and fragrance industries